History of "Aspabaraq" Castle (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is mainly written about the Asparaq castle, which is one of the historical monuments, based on historical sources, about its appearance and historical significance. At the same time, the social significance of this historical monument was analyzed in depth, and information was given about its special place in the history of mankind